PENGARUH INVESTASI, KEPADATAN PENDUDUK, DAN JUMLAH TRANSPORTASI TERHADAP DEGRADASI LINGKUNGAN DI INDONESIA - Hasni, David Anugerah; Azhar, Zul (Universitas Negeri Padang, 2021)
This research aims to prove and analyze the effect of total investment, population density and the amount of transportation on environmental degradation in Indonesia. The data used is obtained from the worbank website and the National Statistics Agency. The data used is time series data with a time sequence from 1988 to 2018. The method of analysis used in this research is multiple linear regression processed using SPSS. Based on the results of hypothesis testing, it is found that total investment and population density have no significant effect on environmental degradation in Indonesia, while the amount of transportation has a significant effect on environmental degradation in Indonesia.